2019
DOI: 10.1016/j.ejps.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent HPLC analysis of the product ratio of enzymatically reduced prodrug CB1954 by a modified and immobilised nitroreductase

Abstract: Time dependent HPLC analysis of the product ratio of enzymatically reduced prodrug CB1954 by a modified and immobilised nitroreductase Gwenin,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…NfnB The comparison of the NfnB-Cys:CPP conjugates with our previously reported free NfnB-Cys enzyme kinetics [29] and indicated an alteration in the enzyme's kinetic behaviour, for both NfnB-Cys:CPP conjugates. The k cat and K m values presented are the apparent (app) values measured at 400 µM NADH.…”
Section: Conjugatementioning
confidence: 54%
See 3 more Smart Citations
“…NfnB The comparison of the NfnB-Cys:CPP conjugates with our previously reported free NfnB-Cys enzyme kinetics [29] and indicated an alteration in the enzyme's kinetic behaviour, for both NfnB-Cys:CPP conjugates. The k cat and K m values presented are the apparent (app) values measured at 400 µM NADH.…”
Section: Conjugatementioning
confidence: 54%
“…Previously we have shown that after a 30 min reaction time, NfnB-Cys reduced CB1954 to two products (namely 2-NHOH and 4-NHOH) at a ratio of 32:68 respectively [29]. Following the same procedure, conjugates of NfnB-Cys and the CPPs at a 1:1 molar ratio were tested for their ability to reduce CB1954.…”
Section: Hplc Profiles Of Nfnb-cys and Nfnb-cyse:cpp Reaction Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interesting application, Ball et al used a nitroreductase (NfnB) with an engineered histidine and cysteine tag (NfnB-cys) immobilized on an AuNP to activate the prodrug 5-(aziridin-1-yl)-2,4-dinitrobenzamide (CB1954) for potential application in Directed Enzyme Prodrug Therapy (DEPT) for cancer treatment [117]. The prodrug has two nitro groups at the 2 and 4 positions that can be reduced to NHOH.…”
Section: Enzyme Immobilization On Aunpsmentioning
confidence: 99%